EFFECT OF E-RECRUITMENT ON THE GROWTH OF PHARMACEUTICAL COMPANIES IN ILORIN, KWARA STATE - Nurudeen Bello Ahmed; Rabiat Omoshalewa Bashir (Malete Journal of Accounting and Finance)
The world is classified a global village due to the development of the internet. Technology as it is often described has taken the space for which people based their survival, including profit-oriented organisations. This study focused on examining the effect of e-Recruitment on the growth of pharmaceutical companies in Ilorin, Kwara State. The study employed survey research design through the use of self-administered questionnaire. The study had a population of one hundred and sixty (160) managerial staff of the selected pharmaceutical firms in Kwara State. Data was analysed using descriptive and inferential statistics. With the aid of Correlation and Regressions Analysis and in order to determine and explain the variables used, the study found that; e-recruitment has positive effects on business growth. This is shown by the probability value of 0.081, 0.051 and 0.053 which is less than the chosen 10% significance level. The study therefore concludes among others that pharmaceutical firms should maintain or adopt the use of e-recruitment in order to boost the company revenue or profit profile. This is because e-recruitment as a new development has helped drop the cumbersome nature of manual recruitment processes to a more robust, transparent and technological exercise. The study therefore recommends that pharmaceutical companies using e-recruitment can maintain their operations and those yet to key into it should adopt he technology.